Gender Analysis, Milk Value Chain, Kabale Uganda. Kabale: Kabale University. - Tugume, Samuel (Kabale University, 2024)
The study was carried out to determine gender involvement in the milk value chain in the Kabale district. The specific objectives of the study involved ascertaining the activities involved by the male and female genders in the milk value chain, who controls resources and decision-making, and the challenges faced by the male and female genders in the milk value chain in the study area. A multi-stage sampling procedure was used to select 90 respondents for the study. An online survey questionnaire was developed and administered to the male and female gender involved in the milk value chain. The findings of the study show that the mean of the female gender was 32 years while that of the male gender was 38 years. Though most of the respondents were literate, their literacy level was low with more than half of the male and female respondents not attaining beyond a secondary education. A higher proportion of the male gender (35.5%) owned herds as against 17.7% of the female gender. The few females that owned herds had fewer numbers when compared to the males. Most of the female respondents were involved in pasteurization. The male gender was more involved in the distribution of milk to retailers and consumers than the male gender, both the male and the female genders were involved in milk consumption. None of the female genders engaged in quality assurance, product integrity, and compliance with standards. While a few of the male respondents engaged in quality assurance. the male gender has control over land and livestock. Feed and fodder, labor, technology and equipment, financial capital, and income than the female respondents Also, 72.2% of men have access to decision-making on land, 71.1% on livestock, feed and fodder, technology and equipment, and knowledge and experts respectively. They also were involved in decision-making on water, labor, income, and marketing, when compared to the female gender. While comparing the challenges faced by the male and female genders, men have better access to education and training than women(4.2 vs. 2.2) women perform a larger share of unpaid or underpaid labour(4.6 vs. 1.7), women face greater challenges in accessing markets and value-addition opportunities. (4.6 vs. 2.1); women likely have less time to dedicate solely to farm activities (4.2 vs. 2.3); men hold more decision-making authority (3.9 vs. 2.7) while both genders might face challenges in accessing these services, but women are still disadvantaged (4.7 vs. 4.5). The study reveals a need for interventions to empower women and ensure their equitable participation. There is a need to Advocate for legal reforms or programs that guarantee women's rights to own land or have secure tenancy agreements. Efforts should be made to facilitate access to credit or microloans specifically for women to purchase dairy cows. Encourage women's groups for collective ownership and management of breeding stock. There is a need to Invest in infrastructure to reduce women's workload and free up their time for dairy activities. The government and NGOs should provide training programs focused on improved dairy farming practices, animal health, hygiene, and milk quality for women. women should be trained in marketing strategies to connect directly with consumers or access better market opportunities for their milk production. There is a need to support the formation and capacity-building of women's dairy cooperatives. Women should be equipped with leadership skills to advocate for their rights and participate effectively in decision-making processes within households and dairy communities. The government should consider the specific needs and contexts of different regions within Uganda while designing interventions and also promote innovation and exploring technological solutions that can address women's time constraints and labor burdens.